Математическая модель и анализ импульсного режима работы линейного электродвигателя при независимом питании его обмоток - Милых, Владимир Иванович; Ткаченко, Сергей Валериевич (НТУ "ХПИ", 2011)
Сформулирована математическая модель линейного электродвигателя, возбуждающего колебания земной коры при поиске полезных ископаемых, соответствующая режиму ударного силового импульса. Ее особенностью является наличие нелинейных трехпараметрических функций дифференциальных индуктивностей и взаимоиндуктивностей обмоток, а также электромагнитной силы взаимодействия реактора и якоря.

A linear electric motor is intended for excitation of vibrations of the earth's crust at the search of minerals. His mathematical model is formulated. She corresponds the mode of shock power impulse. Its feature is a presence of nonlinear functions of differential own and mutual inductances windings. These functions depend on three parameters. The same is function of electromagnetic force which operates on a reactor and anchor
Mathematical model and analysis of the impulsive mode of operations of linear electric motor at the independent feed of his windings
Keywords: линейный импульсный электродвигатель; электромагнитная сила; трехпараметрические функции; сейсмические колебания; программа FEMM; linear impulsive electric motor; own inductance; mutual inductance; electromagnetic force; functions of three parameters